THE INFLUENCE OF CONSUMER BEHAVIOR ON CONSUMER PURCHASE DECISIONS THROUGH BUYING INTEREST AND BUYING HABITS AS INTERVENING FACTORS - larbi el Hadi; Yunelly Asra (Jurnal Al-Iqtishad, 2025)
This study aims to analyze the influence of consumer behavior on purchasing decisions with buying interest and buying habits as intervening variables at the local retailer A Bee Mart in Bengkalis. This study uses an associative quantitative approach with a survey method. The sample size was 100 respondents using a purposive sampling technique. Data collection was carried out through a questionnaire based on a Likert Scale of 1–5. Data analysis used SmartPLS version 4. The results showed that consumer behavior has a positive and significant effect on purchasing decisions, both directly and indirectly through intervening variables. The variable of buying interest proved to be a link that strengthens the relationship between consumer behavior and purchasing decisions, where consumers with positive perceptions of the product showed a higher intention to purchase. Meanwhile, buying habits also have an important role as a mediating variable, indicating that repeat purchases at A Bee Mart are triggered by positive experiences and consumer attachment to the store